2014
DOI: 10.1080/15424065.2014.938999
|View full text |Cite
|
Sign up to set email alerts
|

Discovery Tool vs. PubMed: A Health Sciences Literature Comparison Analysis

Abstract: The East Carolina University libraries, though administratively separate, jointly subscribe to and collaborate on enhancements for a shared instance of the Summon Discovery Service. Based on usage, enhancements to the discovery tool over the past few years, and the perceived ease of searching in Summon, health sciences librarians have questioned whether Summon could now be considered a legitimate competitor to PubMed. This article includes results of a citation comparison between the two databases and the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Wildgaard and Lund (2016, p. 670) argued that PubMed has been traditionally “the main database for searching biomedical literature and constructing systematic reviews.” By the end of 2017, the PubMed database included around 27.5 million documents, representing more than 7000 academic journals (Williamson & Minter, 2019). Thus, PubMed was the logical choice to conduct the analysis because of its accessibility to any researcher with Internet access and because of its breadth and depth of coverage related to multiple topics (Ketterman & Inman, 2014). Data collected included authors names, title of the article, journal, type of publication, abstract of the article, institution's name, and document's number.…”
Section: Methodsmentioning
confidence: 99%
“…Wildgaard and Lund (2016, p. 670) argued that PubMed has been traditionally “the main database for searching biomedical literature and constructing systematic reviews.” By the end of 2017, the PubMed database included around 27.5 million documents, representing more than 7000 academic journals (Williamson & Minter, 2019). Thus, PubMed was the logical choice to conduct the analysis because of its accessibility to any researcher with Internet access and because of its breadth and depth of coverage related to multiple topics (Ketterman & Inman, 2014). Data collected included authors names, title of the article, journal, type of publication, abstract of the article, institution's name, and document's number.…”
Section: Methodsmentioning
confidence: 99%
“…PubMed, provided by the National Library of Medicine, is considered a gold standard in health sciences, because it contains one of the largest biomedical indexes in the world and has powerful searching capabilities with its controlled vocabulary and term mapping. Ketterman & Inman (2014) compared the number of citations in PubMed to their discovery platform Summon, which they shared with all of East Carolina University. They concluded that Summon was a good supplement but not a replacement to searching PubMed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies such as Ketterman and Inman (2014) have sought to compare WSDs directly with traditional bibliographic databases. However the authors of this study highlight research into typical library user behaviour that shows a preference for Google-style searching over traditional methods due to ease, efficiency, and relevance ranking.…”
Section: Commentarymentioning
confidence: 99%